Congenital anomalies in childhood encountered during clinical practice by an otorhinolaryngologist - Goswami, Abhilasha; Sharma, Kalpana; Biswas, A. K. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The otorhinolaryngological developmental anomalies are predisposed by a number of factors like genetic factors, intrauterine infection and maternal nutritional deficiencies. The otorhinolaryngological anomalies may be associated with other systemic maldevelopments. Methods: A total of 134 cases of congenital otorhinolaryngological childhood anomalies, fulfilling the inclusion criteria, who presented to the out-patient department were examined for a period of one year from January 2019, and were included in the study. They were thoroughly evaluated by undertaking a detailed history and clinical examination. Whenever required, additional investigations were performed. After carrying out the necessary investigations, the cases were either managed surgically or conservatively. Data was evaluated using proper statistical tools. Results: Out of the 134 cases, 64.9% were male and 35.1% were female. In our study, 116 cases presented in the first decade of life and 18 cases presented in the second decade of life, up to 18 years of age. The most common childhood congenital anomaly was congenital deafness, which accounted for 44% of all cases. Conclusions: Encountering cases of congenital anomalies in childhood is quite common during practice of otorhinolaryngology. Parents of the suspected children should be counselled properly to investigate other systemic anomalies. Medical and surgical management of the condition should be undertaken hand in hand with adequate counselling.